2019
DOI: 10.1016/j.waojou.2019.100077
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-activated chloride channel regulator 1 (CLCA1): More than a regulator of chloride transport and mucus production

Abstract: CLCA1 is a member of the CLCA (calcium-activated chloride channel regulator) family and plays an essential role in goblet cell mucus production from the respiratory tract epithelium. CLCA1 also regulates Ca2+-dependent Cl− transport that involves the channel protein transmembrane protein 16A (TMEM16A) and its accessary molecules. CLCA1 modulates epithelial cell chloride current and participates in the pathogenesis of mucus hypersecretory-associated respiratory and gastrointestinal diseases, including asthma, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 92 publications
(147 reference statements)
0
30
0
Order By: Relevance
“… 57 CLCA4 is a class of calcium-activated chloride channel regulator. 58 Research has shown that CLCA1 is connected with the development of colorectal cancer. 59 However, the function and mechanism of ADAMDEC1 and CLCA1 in BC are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“… 57 CLCA4 is a class of calcium-activated chloride channel regulator. 58 Research has shown that CLCA1 is connected with the development of colorectal cancer. 59 However, the function and mechanism of ADAMDEC1 and CLCA1 in BC are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…CLCA1 therefore takes part in mucus processing and in the structural arrangement of the mucus (26). In addition, CLCA1 participates in innate immune responses by altering cytokine and chemokine production (25).…”
Section: Discussionmentioning
confidence: 99%
“…The von Willebrand factor is a large multimeric glycoprotein found in blood plasma, and mutation of VWA causes bleeding disorders ( Ruggeri and Ware, 1993 ). CLCA family members have been reported in different species, including human (four genes from hCLCA1 to hCLCA4 ), mouse and rat (eight homologs from mCLCA1 to mCLCA8 ), and cow [ bCLCA1 , bCLCA2 (Lu-ECAM-1), bCLCA3 , and bCLCA4 ] ( Liu and Shi, 2019 ). There are six ortholog genes documented in zebrafish: CLCA1 , CLCA5.1 , CLCA5.2 , CLCA1-201 , CLCA1-203 , and CLCA5.1-201 ( Howe et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%